2018
DOI: 10.3389/fphar.2018.00173
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Protein Arginine Methyltransferase 5 Inhibitor in Non-small Cell Lung Cancer by Structure-Based Virtual Screening

Abstract: Protein arginine methyltransferase 5 (PRMT5) is able to regulate gene transcription by catalyzing the symmetrical dimethylation of arginine residue of histone, which plays a key role in tumorigenesis. Many efforts have been taken in discovering small-molecular inhibitors against PRMT5, but very few were reported and most of them were SAM-competitive. EPZ015666 is a recently reported PRMT5 inhibitor with a new binding site, which is different from S-adenosylmethionine (SAM)-binding pocket. This new binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This might also explain why the addition of high doses of EPZ015666 does not further decrease proliferation of T cells cultured at high MTA concentrations. Therefore, the development of more potent and/or MTA-selective PRMT5 inhibitors is necessary and is focus of ongoing studies (49,50). However, we demonstrated that PRMT5 inhibition suppresses human CD8 þ T cells, with the synthetic PRMT5 inhibitor EPZ015666 acting similar to MTA, a naturally occurring PRMT5-inhibiting molecule.…”
Section: Discussionmentioning
confidence: 91%
“…This might also explain why the addition of high doses of EPZ015666 does not further decrease proliferation of T cells cultured at high MTA concentrations. Therefore, the development of more potent and/or MTA-selective PRMT5 inhibitors is necessary and is focus of ongoing studies (49,50). However, we demonstrated that PRMT5 inhibition suppresses human CD8 þ T cells, with the synthetic PRMT5 inhibitor EPZ015666 acting similar to MTA, a naturally occurring PRMT5-inhibiting molecule.…”
Section: Discussionmentioning
confidence: 91%
“…The binding free energies of MS402 and BRD4‐BDs were analyzed by the molecular mechanics generalized born surface area method . Herein, a total of 500 snapshots were extracted from the last 50 ns MD trajectory and calculated as follows: normalΔGMMGBSA=Gcomplex()GBD+GMS402 normalΔGMMGBSA=normalΔHTnormalΔSnormalΔEMM+normalΔGsolTnormalΔS normalΔEMM=normalΔEelectrostatic+normalΔEvdw normalΔGsol=normalΔGGB+normalΔGSA=normalΔGGB+γ0.25emSASA Where Δ G MMGBSA denoted the binding free energy between BD and MS402 and could be divided into three terms: molecular mechanical energy (Δ E MM ), solvation energy (Δ G sol ), and entropy (− T Δ S ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 200 ns MD simulations at a temperature The binding free energies of MS402 and BRD4-BDs were analyzed by the molecular mechanics generalized born surface area method. 27,[44][45][46] Herein, a total of 500 snapshots were extracted from the last 50 ns MD trajectory and calculated as follows:…”
Section: Simulations and Thermodynamic Calculationsmentioning
confidence: 99%
“…Its higher potency derivative, GSK3326595, is currently in clinical trials (20,21). Many other PRMT5is have been developed (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), of which JNJ64619178, PF-06939999, and PRT543, are also in clinical trials (31)(32)(33). Notably, some work through distinct mechanisms from EPZ015666 and GSK3326595, for example JNJ64619178 targets the SAM binding domain (21).…”
Section: Significancementioning
confidence: 99%